2009
DOI: 10.1007/s12571-009-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

A community food system analysis as formative research for a comprehensive anemia control program in Northern Afghanistan

Abstract: Afghanistan, Women, Anemia, Iron, Food, Social network,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…On average, about 40% of iron content in animal source foods is heme iron, and 60% is non-heme iron, whereas 100% of plant source foods is non-heme iron [ 43 ] The bioavailability of heme iron has been estimated to range between 15 and 35%, while the bioavailability of non-heme iron has been found to vary between 2 and 20% [ 44 , 45 ]. Dairy, tea and phytate-containing foods such as grains and legumes are potentially important non-heme iron absorption inhibitors in this context [ 46 , 18 ], whereas meat and ascorbic acid sources are key non-heme iron absorption enhancers [ 47 ]. The relatively high bioavailability of meat compared to non-heme sources of iron, and its ability, even in small doses, to enhance the bioavailability of non-heme iron [ 47 ] makes it a more important dietary factor in combating anemia than overall dietary contributions might suggest.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On average, about 40% of iron content in animal source foods is heme iron, and 60% is non-heme iron, whereas 100% of plant source foods is non-heme iron [ 43 ] The bioavailability of heme iron has been estimated to range between 15 and 35%, while the bioavailability of non-heme iron has been found to vary between 2 and 20% [ 44 , 45 ]. Dairy, tea and phytate-containing foods such as grains and legumes are potentially important non-heme iron absorption inhibitors in this context [ 46 , 18 ], whereas meat and ascorbic acid sources are key non-heme iron absorption enhancers [ 47 ]. The relatively high bioavailability of meat compared to non-heme sources of iron, and its ability, even in small doses, to enhance the bioavailability of non-heme iron [ 47 ] makes it a more important dietary factor in combating anemia than overall dietary contributions might suggest.…”
Section: Resultsmentioning
confidence: 99%
“…Neither the AMICS nor the NRVA survey contains information on iron supplementation, and so this cannot be checked directly. However, Levitt et al [ 18 ] found that just over 50% of women in their sample had received iron-folate supplements during their last pregnancy. The World Bank review of nutrition in Afghanistan [ 15 ] reports that iron and folic acid supplementation is available through prenatal care services, and that care coverage is 36%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2016, 44.6% of the population was food insecure and 30.1% had protein deficiency (CSO, 2018). Levitt et al (2009) conducted formative research in northern Afghanistan to understand iron‐rich food access and consumption by populations living in irrigated and rain‐fed zones. In both zones, summer and winter diets contained some iron‐rich foods, although differences were found between communities in the summer, such as meat consumption no more than once a week in the rain‐fed zone compared with twice a week in the irrigated zone, with the increased consumption tied to larger social occasions as a means of honouring guests.…”
Section: Resultsmentioning
confidence: 99%
“…Ten years ago, Johnecheck and Holland (2007) envisaged a multisectoral approach to improving malnutrition in Afghanistan, while various other research outcomes have identified gaps between the agricultural and nutrition sectors, and highlighted the significance of food-based approaches to improving nutrition (Levitt, Pelletier and Pell 2009a;Levitt et al 2009b;Levitt et al 2010;Levitt et al 2011). Nevertheless, current policies do not emphasise the role of agriculture and food-based strategies for improving nutrition.…”
Section: The Afghan Contextmentioning
confidence: 99%